Why Knowledge Matters in Curriculum : a Social Realist Argument. - Wheelahan, Leesa (New studies in critical realism and education., 2012)
What should we teach in our schools and vocational education and higher education institutions? Is theoretical knowledge still important??This book argues that providing students with access to knowledge should be the raison d'être of education. Its premise is that access to knowledge is an issue of social justice because society uses it to conduct its debates and controversies. Theoretical knowledge is increasingly marginalised in curriculum in all sectors of education, particularly in competency-based training which is the dominant curriculum model in vocational education in many countries. T.